Cultivation the Characters of Discipline and Honesty Through the Class Agreement Bulletin Board - Amalia, Adilla Salsa; Utomo, Arief Cahyo (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to describe the application of a class agreement bulletin board to foster the values of discipline and honesty. This research employed a qualitative method with a case research design conducted at MI Muhammadiyah Karanglo. The research participants consisted of six students from class V and the homeroom teacher of class V. Data collection techniques included observation, interviews, and documentation. Data analysis techniques involved data reduction, data presentation, and drawing conclusions. The research findings are as follows: (1) The application of the class agreement bulletin board consists of 10 mutually agreed-upon rules, with consequences for those who violate them; (2) The implementation of the class agreement bulletin board effectively fosters the values of discipline and honesty through daily practice; (3) Challenges that arise include differences of opinion, internal student factors, and insufficient supervision from the teacher. The proposed solution is to conduct weekly evaluations. Thus, this research concludes that the application of the class agreement bulletin board functions effectively on a daily basis, fostering a sense of discipline and honesty among students at school. This is evidenced by the students consistently adhering to the rules and carrying out the agreed-upon consequences.